2017
DOI: 10.1016/j.appet.2016.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Habitual chocolate intake and type 2 diabetes mellitus in the Maine-Syracuse Longitudinal Study: (1975–2010): Prospective observations

Abstract: Compounds in cocoa and chocolate have established cardiovascular benefits, including beneficial effects on insulin resistance, a risk factor for type 2 diabetes mellitus. The aims of this study was to investigate relations between habitual chocolate intakes and diabetes mellitus. Cross-sectional and prospective analyses were undertaken on 953 community-dwelling participants (mean age 62 years, 59% women) from the Maine-Syracuse Longitudinal Study (MSLS). Habitual chocolate intakes, measured using a food freque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 29 publications
0
28
1
2
Order By: Relevance
“…Two prospective observational studies were included for all-cause mortality [28,29], 9 reports (10 studies) for CHD [28,[30][31][32][33][34][35][36][37], 8 studies for stroke [28,30,31,33,36,[38][39][40], 6 studies for heart failure [28,35,[41][42][43][44], 6 studies for T2D [23,[45][46][47][48][49], and 2 studies for CRC [50,51], and hypertension [52,53], respectively (ESM Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Two prospective observational studies were included for all-cause mortality [28,29], 9 reports (10 studies) for CHD [28,[30][31][32][33][34][35][36][37], 8 studies for stroke [28,30,31,33,36,[38][39][40], 6 studies for heart failure [28,35,[41][42][43][44], 6 studies for T2D [23,[45][46][47][48][49], and 2 studies for CRC [50,51], and hypertension [52,53], respectively (ESM Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…All studies reported cross-sectional data. Five publications analysed data previously collected in other studies, [24,[25][26][27][28] with three reporting baseline data collected prior to conducting an intervention trial [25,27,28]. A total of 10, 672 individuals participated in the 11 studies, 9, 718 of which had T2DM.…”
Section: Resultsmentioning
confidence: 99%
“…On the test group, greater reductions were observed in the clinical variables after the consumption of 70% cocoa chocolate with Although the use of 70% cocoa chocolate added with the acids did not cause significant differences in the clinical variables during the four weeks of observation, the clinical results of the test group showed improvement in relation to the group that consumed 70% cocoa without the acids during the same period. However, several authors (Crichton et al, 2017;Souza et al, 2017) have reported on the ability of 70% cocoa chocolate to improve the results of clinical testing of individuals.…”
Section: Clinical Trialmentioning
confidence: 99%